Relationship of Urine Acidity to The Risk of Candidiasis Infection in Pregnant Mothers - Aini, Aini; Ustiawaty, Jumari; Wahyuni, Devi (JSN : Jurnal Sains Natural, 2023)
Candidiasis is a disease caused by fungi and the most common cause is candida albicans. The aim of this study was to measure the relationship between the degree of urine acidity and the risk of candidiasis infection in pregnant women. The benefit of research is to determine the degree of acidity on the incidence of candidiasis in pregnant women. The results of research from 42 urine samples from pregnant women found urine with an acidic pH of 30 urines or 71.4% and from these 30 samples 19 urine samples were found to be positive for Candida albicans. A neutral pH was found in 5 urines with the sample test results not finding Candida albicans, but 1 sample was found with the fungus Candida Sp. The results of the urine measurements found 7 urine with an alkaline pH and no Candida albicans was found, but overall Esterococcus bacteria were found in the urine with a neutral and alkaline pH and no Candida albicans was found.